Through scaffold modification to 3, 5-diaryl-4, 5-dihydroisoxazoles: new potent and selective inhibitors of monoamine oxidase B. (1st January 2017) - Meleddu, Rita; Distinto, Simona; Cirilli, Roberto; Alcaro, Stefano; Yanez, Matilde; Sanna, Maria Luisa; Corona, Angela; Melis, Claudia; Bianco, Giulia; Matyus, Peter; Cottiglia, Filippo; Maccioni, Elias
Abstract: 3, 5-Diaryl-4, 5-dihydroisoxazoles were synthesized and evaluated as monoamine oxidase (MAO) enzyme inhibitors and iron chelators. All compounds exhibited selective inhibitory activity towards the B isoform of MAO in the nanomolar concentration range. The best performing compound was preliminarily evaluated for its ability to bind iron II and III cations, indicating that neither iron II nor iron III is coordinated. The best compounds racemic mixtures were separated and single enantiomers inhibitory activity evaluated. Furthermore, none of the synthesised compounds exhibited activity towards MAO A. Overall, these data support our hypothesis that 3, 5-diaryl-4, 5-dihydroisoxazoles are promising scaffolds for the design of neuroprotective agents.